Expectancy biases in fear and anxiety and their link to biases in attention. (December 2015) - Aue, Tatjana; Okon-Singer, Hadas
Abstract: Healthy individuals often exhibit prioritized processing of aversive information, as manifested in enhanced orientation of attention to threatening stimuli compared with neutral items. In contrast to this adaptive behavior, anxious, fearful, and phobic individuals show exaggerated attention biases to threat. In addition, they overestimate the likelihood of encountering their feared stimulus and the severity of the consequences; both are examples of expectancy biases. The co-occurrence of attention and expectancy biases in fear and anxiety raises the question about causal influences. Herein, we summarize findings related to expectancy biases in fear and anxiety, and their association with attention biases. We suggest that evidence calls for more comprehensive research strategies in the investigation of mutual influences between expectancy and attention biases, as well as their combined effects on fear and anxiety. Moreover, both types of bias need to be related to other types of distorted information processing commonly observed in fear and anxiety (e.g., memory and interpretation biases). Finally, we propose new research directions that may be worth considering in developing more effective treatments for anxiety disorders. Highlights: We summarize evidence for attention bias and expectancy bias in health and anxiety. Possible causal relations between these processing biases were rarely investigated. New research venues are proposed. This review aims at stimulating future research in order to provide effective therapy.